(NrASUL gAMZATOW(B. (NsOBRANIE SO^INENIJ W PQTI TOMAH (B/ s - (NgAMZATOW(B, (NrASULs ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURAs)
(NtOM (B1 - (NSTIHOTWORENIQ (B((NIZ KNIG (B"(NzEMLQ MOQ(B", "(NpESNI GOR(B", "(NgOD MOEGO ROVDENIQ(B", "(NsTIHOTWORENIQ(B", "(NdETI DOMA ODNOGO(B", "(NnOWAQ WSTRE^A(B", "(Nw GORAH SERDCE MOE(B"), (NPO\MY (B"(NgOD MOEGO ROVDENIQ(B", "(NrODINA GORCA(B", "(NgORQNKA(B", (NI DR(B. (NtOM (B2 - (NSTIHOTWORENIQ (B((NIZ KNIG (B"(NwYSOKIE ZWEZDY(B", "(Ni ZWEZDA S ZWEZDO@ GOWORIT(B", "(NmULATKA(B", "(NoB]IJ HLEB(B", "(N~ETKI LET(B", "(NtRETIJ ^AS(B", "(NtAINSTWENNOSTX(B"), (NPO\MY (B"(NzWEZDA dAGESTANA(B", "(NcELU@ VENSKIE RUKI(B", "(NpQTX PALXCEW(B", "(NkOLOKOL hIROSIMY(B". (NtOM (B3 - (NSTIHOTWORENIQ (B((NWOSXMISTI[IQ(B, (N^ETWEROSTI[IQ(B, (NNADPISI(B, (N\LEGII(B, (N\PIGRAMMY(B, (NSONETY(B, "(NgORSKIE SONETY O L@BWI(B", (NLEGENDY I SKAZANIQ(B), (NPO\MY (B"(NrAZGOWOR S OTCOM(B", "(NbEREGITE MATEREJ(B", "(NbRAT(B". (NtOM (B4 - "(NmOJ dAGESTAN(B". (NtOM (B5 - (NSTIHOTWORENIQ (B((NIZ KNIG (B"(NpOSLEDNQQ CENA(B", "(NoSTROW vEN]IN(B", (NSTIHI RAZNYH LET(B, (NAWTOGRAFY I NADPISI(B), (NPO\MY (B"(NpOSLEDNQQ CENA(B", "(NbATYRAJ(B", "(NoSTROW vEN]IN(B", (NSTATXI I WYSTUPLENIQ IZ KNIGI (B"(NwERNOSTX TALANTU(B".s
rus
Keywords: (NsTIHOTWORENIQs; (NpO\ZIQ(B, (NPO\MYs; (NkLASSI^ESKAQ PROZAs; (NlIRI^ESKAQ PROZAs -- (NsTATXIs